2010
DOI: 10.1080/10538712.2010.496713
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sexual Abuse/Attack Histories with Bariatric Surgery Patients

Abstract: This study assessed sexual abuse/attack histories in 573 [corrected] bariatric surgery patients using the PsyBari. The prevalence rates found were lower (15.5%, 19.3% of women, 5.2% of men) than other studies that used bariatric surgery patients but consistent with studies that used nonbariatric obese subjects. Furthermore, bariatric surgery patients who disclosed sexual abuse/attack were more likely to disclose physical abuse, psychological problems, psychological treatment, psychiatric medication, and psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
(39 reference statements)
2
20
0
Order By: Relevance
“…As obesity severity increases, the self-reported prevalence of sexual abuse as well as other psychosocial issues rises, although this is not a consistent finding [811]. Previous studies examining the prevalence of sexual abuse in severely obese patients seeking bariatric care have reported a 16–32% prevalence of sexual abuse [12, 13], compared to approximately 4–20% in the general population [1416]. A recent meta-analysis of childhood sexual abuse with 10 million subjects estimates the worldwide prevalence to be 13% [17]; similarly, Canadian studies suggest that self-reported sexual abuse during childhood and adolescence occurred in 4% of males and 13% of females [16].…”
Section: Introductionmentioning
confidence: 99%
“…As obesity severity increases, the self-reported prevalence of sexual abuse as well as other psychosocial issues rises, although this is not a consistent finding [811]. Previous studies examining the prevalence of sexual abuse in severely obese patients seeking bariatric care have reported a 16–32% prevalence of sexual abuse [12, 13], compared to approximately 4–20% in the general population [1416]. A recent meta-analysis of childhood sexual abuse with 10 million subjects estimates the worldwide prevalence to be 13% [17]; similarly, Canadian studies suggest that self-reported sexual abuse during childhood and adolescence occurred in 4% of males and 13% of females [16].…”
Section: Introductionmentioning
confidence: 99%
“…substance-related disorders, physical abuse and suicidal ideations [45,46,47]. Substance-related disorders such as alcohol abuse pose a particular risk as they exacerbate the lack of coping skills [48] and control.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, others have proposed the utilization and exploration of more newly developed instruments such as the Personality Assessment Inventory (PAI - Corsica, Azarbad, McGill, Wool, & Hood, 2010), the PsyBari (Mahony, 2010), and the Revised Master Questionnaire (Corsica, Hood, Azarbad, & Ivan, 2011). Corsica et al demonstrated that the PAI has sound psychometric properties for use with the bariatric population (Corsica et al, 2010).…”
Section: T H U S F a R I T A P P E A R S T H A T D A T A F R O M T mentioning
confidence: 99%
“…The PsyBari is a self-report survey comprised of questions designed to assess constructs that were thought by the author and "other bariatric surgery professionals" to be important to measure preoperatively (Mahony, 2010). These include surgical motivation, emotional eating, anger, binge eating, obesity-related depression, weight-related social impairment, knowledge of postsurgical dietary restrictions, substance/alcohol abuse, and surgical anxiety.…”
Section: T H U S F a R I T A P P E A R S T H A T D A T A F R O M T mentioning
confidence: 99%
See 1 more Smart Citation